Supply chain collaboration among Malaysian SME manufacturers - Pakir Mohamed, Mohamed Ismail (2012)
Malaysian 3rd Industrial Master Plan was developed to improve the country global competitiveness by positioning Malaysia as a major manufacturing hub and service provider in the global supply chain. To achieve this, it is suggested that Malaysian manufacturers especially SME should be involved in supply chain collaboration in their business operations. However, it is discovered that there are very few reported research on the supply chain collaboration activities among Malaysian SME manufacturers. The objective of this research is to uncover the supply chain collaboration activities among Malaysian SME manufacturers with their trading partners. This is to be done by determining the level of supply chain collaboration of Malaysian SME manufacturer and investigating the reason Malaysian SME manufacturers supply chain collaborations is at that level. In order to achieve the above objective, a mixed method of quantitative approach using survey method is employed to determine the level of supply chain collaboration and qualitative approach using personal interview method is employed to find out the reason for why Malaysian SME manufacturers’ supply chain collaboration is at that level. This research discovered that the supply chain collaboration of Malaysian SME manufactures with their trading partners is at minimal level. This is due to their current business relationship that they have with their trading partners do not required them to collaborate at higher level. On the other hand, Malaysian SME manufacturer are willing to have a high level of supply chain collaboration if long term business relationship could be established. Therefore, it is concluded that the type of business relationship or cooperation with trading partners can determine level of supply chain collaboration.